(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Very recently, the concept of θ-hyperbolic sine distance functions has been introduced by Jleli and Samet in [14]. In this work, we prove some related fixed points results for several classes of multivalued mappings including manageable functions on metric spaces.